Examining the Relationship Between School Administrators’ Chaotic Leadership and Organizational Anomie According to Teachers’ Perceptions - Şallı, Duygu (GLOBETS 2023 Educational Technology and Science Research, 2024)
In the field of leadership, chaos is a critical juncture where principles blur, demanding that a leader's actions take precedence in bewildering rather than clear-cut scenarios. Such unpredictable circumstances call for chaotic leadership, marked by its dynamic nature. Navigating leadership in chaos is arduous yet essential for effective guidance. It entails steering teams through tumultuous environments, where incessant change renders conventional methods obsolete. Leaders in chaotic situations must possess unique skills, including the capacity to handle complexity, and the ability to stabilize and guide their entire team. Organizational anomie often emerges in these chaotic contexts, characterized by a dearth of norms and values, breeding uncertainty among employees. Addressing such environments necessitates a specific leadership style. This study delves into the correlation between school administrators' chaotic leadership and organizational anomie from the perspective of teachers. Utilizing a relational survey model, a quantitative research approach, the study focuses on schools under the Ministry of National Education across various Istanbul districts. Data was gathered using the "Chaotic Leadership Scale" and "Organizational Anomie Scale." The findings reveal a significant inverse relationship between managers' chaotic leadership and organizational anomie, leading to recommendations based on these insights.